A Numerical Treatment of a Mathematical Model of Ground Water Flow in Rice Field near Marine Shrimp Aquaculture Farm - N. Pochai; N. Pongnoo (My University, 2012)
The high level salinity in soil is a main problem of a plant grows less in rice field near marine shrimp aquaculture farm. The salinity in soil and ground water flow are required for soil quality assessments. The modeling often involves numerical methods to solve the equations. In this research, two mathematical models are used to simulate the salinity in the ground with varied flow velocity. The first is a potential flow model that provides the velocity field of the ground water flow. The second is a dispersion model, where the commonly used governing factor is the twodimensional dispersion equation that gives the salinity fields. In the simulation process, we used the finite difference method for the both models. Finally, we present a numerical simulation that confirms the results of the technique.
Keywords: Paddy field; Innovations in Aquaponics and Hydroponics Systems